2012
DOI: 10.1103/physrevb.86.235431
|View full text |Cite
|
Sign up to set email alerts
|

Role of functional groups in surface bonding of planarπ-conjugated molecules

Abstract: The trends in the bonding mechanism of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA) to the Ag(111), Ag(100), and Ag(110) surfaces were analyzed on the basis of data obtained from x-ray standing waves and dispersion-corrected density functional theory. Of importance are the attractive local O-Ag bonds on the anhydride groups. They are the shorter, the more open the surface is, and lead even to partly repulsive interactions between the perylene core and the surface. In parallel, there is an increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
114
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(141 citation statements)
references
References 50 publications
24
114
3
Order By: Relevance
“…First, the work function of the metal controls both adsorption height and LUMO binding energy: if the work function is low, the spatial extent of the charge spill out is small. This favours both small adsorption heights 5,[12][13][14] andassuming vacuum level alignment-large LUMO binding energies. Note that the push-back effect, that is, the Pauli repulsion of the electronic charge spill out of the metal caused by the approaching molecule, even strengthens this correlation: a larger push-back tends to reduce adsorption height and work function further, yielding even larger orbital binding energies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the work function of the metal controls both adsorption height and LUMO binding energy: if the work function is low, the spatial extent of the charge spill out is small. This favours both small adsorption heights 5,[12][13][14] andassuming vacuum level alignment-large LUMO binding energies. Note that the push-back effect, that is, the Pauli repulsion of the electronic charge spill out of the metal caused by the approaching molecule, even strengthens this correlation: a larger push-back tends to reduce adsorption height and work function further, yielding even larger orbital binding energies.…”
mentioning
confidence: 99%
“…Hence, one would expect that a smaller adsorption height should correspond to stronger chemical interaction. Indeed, it was recurrently observed that on more reactive surfaces, where chemical interaction is stronger, the adsorption heights tend to be smaller [1][2][3][4][5][6][7][8][9][10][11][12] . This empirical correlation is often a result of both local and extended (that is, p-) bonds 12 and of the charge spill-out profile above the surface (see below).…”
mentioning
confidence: 99%
“…Analysis of adsorbed PTCDA or NTCDA on Ag(111) [10,20] provided clear evidence of a non-negligible relaxation of Ag surface atoms which did comprise not only an overall contraction of the vertical bonding distance but also introduced an extra corrugation of surface atoms underneath of PTCDA or NTCDA. As shown below, our calculations confirm that this is the case also for the NTCDA c-ML and r-ML phases discussed here.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental value for C-atoms corresponds to averaging over all C-atoms for r -ML. two major contributions, similar to the case of PTCDA monolayers on different Ag surfaces [10]: Specifically, the derived geometry is determined by the interplay between attraction of the functional groups with silver atoms, repulsion of the carbon backbone from the substrate and the ability of the molecule and the surface to accommodate such distortions. The surface and interface state energies (E SS and E IS ) for r-ML and c-ML phases are presented in Table II.…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation